1997
DOI: 10.1111/j.1939-1668.1997.tb00242.x
|View full text |Cite
|
Sign up to set email alerts
|

The Language of Beauty and the Modern Interior: An Approach to Aesthetic Criticism

Abstract: OBJECTIVE: This article presents a critical evaluation of images of the popular American modern environment of the 1940s. THEORETICAL FRAMEWORK: Using content analysis and a close semiological reading of representative images and phrases, the spaces of the modern interior environment in the context of the philosophical writings of Burke (1756), Kant (1790), Ruskin (1849), Downing (1865) and Turner (1991) are examined. Works by these philosophers collectively establish a connection between the concepts of beaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For instance, in the process of color design, Minimalism advocates the use of neutral and cool colors to achieve harmony. Although some bright colors with strong impact will be less used, often bright colors are a manifestation of visual impact [19]. However, it is a minimalist architectural language, emphasizing the openness and continuity of space, thus forming a horizontal architecture, eliminating details to a minimum, and emphasizing the natural light on the white surface.…”
Section: Minimalism In Interior Designmentioning
confidence: 99%
“…For instance, in the process of color design, Minimalism advocates the use of neutral and cool colors to achieve harmony. Although some bright colors with strong impact will be less used, often bright colors are a manifestation of visual impact [19]. However, it is a minimalist architectural language, emphasizing the openness and continuity of space, thus forming a horizontal architecture, eliminating details to a minimum, and emphasizing the natural light on the white surface.…”
Section: Minimalism In Interior Designmentioning
confidence: 99%
“…Stamps III and Nasar (1997) extended on the popular high-style categorization by suggesting that the Mediterranean, Prairie School, Craftsman, Period/French, Contemporary, Farm, Colonial, and Tudor style houses can be considered "popular", while post-modern, contemporary houses built after the 1970s are "high style". Beecher (1997) suggested that although "modernism" was present in every aspect of American post-war material culture, it took a long time for an average consumer to transition between traditional and modern. Leslie and Reimer (2003) proposed that modernism with its simplicity, functionality and flexibility contrasted with the previous aesthetics of craft, decoration, ornamentation and ephemerality.…”
Section: Perception and Preferences Of Architectural Design Stylesmentioning
confidence: 99%